ANALYSIS OF ARGUMENTATION APPLICATION IN TERMS OF LEARNER EXPERIENCES - Et, Sümeyra Zeynep; Gömleksiz, Mehmet Nuri (My University, 2021)
Problem-solving, inquiry, decision-making, and supporting these decisions on solidgrounds are among the skills expected from today’s individuals. Experiences in inquirybased learning environments are crucial for individuals to fulfill these requirements. Inthis context, the research aims to determine the opinions and experiences of 24 scienceteacher candidates who participated in the Argumentation-Based Inquiry (ABI) approachpractices, one of the inquiry activities. Research data were collected through studentjournals. The research aimed to determine the feelings and thoughts of teacher candidatesregarding argumentation practices with student journals. Research data were analyzedusing the content analysis method. Some of the results obtained in the study are asfollows. Teacher candidates stated that the ABI approach made the course entertainingand interesting. They stated that they can actively participate in the process so that theknowledge they have gained regarding the answers to the questions they seek becomesmore meaningful. Further, teacher candidates have often expressed in the journals that they have an important awareness to be able to make claims in this process and to supporttheir claims with evidence, i.e., to defend their ideas.
Keywords: Eğitim; Eğitim Araştırmaları